Preparation method of high-conductivity high-voltage-resistant sulfide electrolyte membrane and high-voltage all-solid-state battery
By introducing a high-voltage resistant halide electrolyte or polymer electrolyte modification layer on the surface of the sulfide electrolyte membrane, the problem of unstable sulfide electrolyte at high voltage is solved, and the stability and energy density of the battery are improved.
Patent Information
- Application Number
- CN202411816623.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Sulfide electrolytes are prone to chemical reactions and interfacial reactions at high voltages, limiting their electrochemical windows and reducing stability.
The design of a double-layer sulfide electrolyte membrane is adopted, and the high-voltage resistance halide electrolyte or polymer electrolyte modification layer is introduced on the surface of the sulfide electrolyte membrane to improve the high-voltage resistance characteristics of the electrolyte membrane.
It effectively alleviates the interface side reaction between sulfide electrolyte and the positive electrode material at high voltage, improves the stability and electrochemical window of the battery, supports higher working voltage, and thus improves the energy density and endurance of the battery.
Smart Images

Figure CN119650824A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries. Specifically, the present invention relates to a sulfide electrolyte membrane and an all-solid-state battery for use in high-voltage application scenarios. Background Art
[0002] All-solid-state batteries use solid electrolytes instead of liquid electrolytes. Solid electrolytes are not as easy to leak or burn as liquid electrolytes, which significantly reduces the risk of fire and explosion in the case of short circuit, impact or overcharge. Solid electrolytes have good stability to high temperature and high voltage, which can effectively reduce the risk of batteries under extreme conditions.
[0003] Sulfide electrolytes have great application prospects in all-solid-state batteries due to their advantages such as high ionic conductivity and low Young's modulus. However, sulfide electrolytes are usually prone to chemical reactions at high voltages, such as reacting with electrode materials or decomposing, which limits their electrochemical window. This reaction may generate harmful byproducts and reduce the stability of the electrolyte. At the same time, when sulfide electrolytes come into contact with high-voltage electrode materials, adverse interfacial reactions may occur, further narrowing their effective electrochemical window. Summary of the invention
[0004] The main purpose of the present invention is to propose a strategy for a high-conductivity, high-voltage-resistant double-layer sulfide electrolyte membrane. By introducing a high-voltage-resistant protective layer, the instability problem of the sulfide electrolyte membrane at high potential is improved. By using a high-voltage-resistant solid electrolyte system such as a halide electrolyte and a polymer electrolyte on the positive electrode side, it helps to alleviate side reactions with the layered positive electrode. The use of a double-layer electrolyte design can further improve the stability of the battery.
[0005] To achieve the above object, the present invention provides a method for preparing a high conductivity high pressure resistant sulfide electrolyte membrane, comprising the following steps:
[0006] (1) Prepare sulfide electrolyte membrane by wet slurry coating or dry electrode technology;
[0007] (2) using a halide electrolyte or a polymer electrolyte as a raw material for a high voltage modification layer, and directly in-situ modifying the prepared modification layer slurry on the surface of a sulfide electrolyte membrane; specifically, the thickness of the modification layer is 1 to 10 μm;
[0008] (3) The modified electrolyte membrane is transferred to a dry atmosphere and baked to obtain an asymmetric high-pressure resistant sulfide electrolyte membrane.
[0009] Preferably, in step (1), the sulfide electrolyte comprises Li 7 P 3 S 11 β-Li3 PS 4 , Li 10 G 2 S 12 , Li 6 PS 5 Cl, Li 6 PS 5 Br, Li 7 P 2 S 8 I. Li 4 PS 4 I. Li 6 PS 5 Cl x Br 1-x , Li 6 PS 5 Cl y I 1-y , Li 6 PS 5 Br z I 1-z One or more of , where x, y, z = 0 to 1.
[0010] Preferably, in step (2), the halide electrolyte used is Li 3 MX 6 , wherein M includes one or more trivalent metals of indium, scandium, yttrium, titanium, and zirconium, and X includes one or more of Cl, Br, and I.
[0011] Preferably, in step (2), during the preparation of the polymer electrolyte modification layer, the selected polymer electrolyte system includes one or more of polyvinyl fluoride (PVDF), polyacrylonitrile (PAN), polyether electrolyte, and cross-linked polyurethane.
[0012] Preferably, in step (2), in the process of preparing the modifying layer slurry, a binder-solvent solution needs to be added, wherein the solvent includes one or more of isopentane, n-pentane, cyclohexane, isooctane, cyclopentane, n-hexane, n-heptane, tetrahydrofuran, toluene, xylene, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dichloromethane, chloroform, n-butyl ether, and anisole, and the binder includes one or more of PIB (polyisobutylene), BR (cis-1,4-butadiene rubber), NBR (nitrile rubber), SEBS (thermoplastic elastomer), SBR (styrene-butadiene rubber), PVDF (polyvinylidene fluoride), PIB (polyisobutylene), SBS (thermoplastic styrene-butadiene rubber), SR (synthetic rubber), HNBR (hydrogenated nitrile rubber), PEVA (polyethylene-vinyl acetate), PMMA (polymethyl methacrylate) and PAA (polyacrylic acid).
[0013] Preferably, in step (2), the selected modification method includes one or more of wet coating, electrostatic spraying, and ultrasonic spraying.
[0014] Preferably, in step (3), a gradient heating program is set during baking. In the first stage, the temperature is raised to 60 - 80°C at a heating rate of 0.1 - 20°C / min and held for 20 - 120 min; in the second stage, the temperature is raised to 90 - 130°C at a heating rate of 0.1 - 20°C / min and held for 2 - 6 h. The present invention preferably selects 60°C and 100°C as the temperature gradient points. The heating rate in the first stage is preferably 1°C / min and held for 60 min; the heating rate in the second stage is preferably 10°C / min and held for 4 h.
[0015] Preferably, the thickness of the high-voltage sulfide electrolyte membrane is 20 - 200 μm, and the room temperature conductivity is 10 -6 ~10 -1 S / cm.
[0016] To achieve the above object, a high-voltage all-solid-state battery proposed by the present invention includes a high-voltage sulfide electrolyte membrane prepared by any of the above methods, a high-voltage positive electrode, and a negative electrode. After stacking the high-voltage positive electrode layer, the high-voltage sulfide electrolyte membrane, and the negative electrode layer in sequence, and performing densification treatment using an isostatic pressing technique, an all-solid-state battery capable of operating at high voltage is obtained. Among them, the modified layer in the high-voltage sulfide electrolyte membrane is close to the positive electrode side.
[0017] Preferably, the high-voltage positive electrode is selected from LiCoO 2 , LiNi a Co b M 1-a-b O 2 and Li 1+n (Mn X Ni Y Co Z ) 1-n O 2 one or more of them, where M is one or several of Mn, Al, Mg, Sn, Y, or Cr, 0 ≤ a < 1, 0 < b ≤ 1, and a + b ≤ 1; 0 < n < 1, 0 < X < 1, X + Y + Z = 1, 0 < Y < X, 0 < Z < X; the negative electrode is selected from one or several of lithium metal alloy, lithium metal, graphite, silicon-carbon composite negative electrode, and silicon; during the densification process of the high-voltage all-solid-state battery by isostatic pressing, the isostatic pressing temperature is 0 - 100°C, the pressure range is 300 - 800 MPa, and the pressing time is 1 - 30 min. Further, during the densification process of the high-voltage all-solid-state battery by isostatic pressing, the isostatic pressing temperature is 80 - 90°C, the pressure range is 400 - 600 MPa, and the pressing time is 5 - 10 min.
[0018] The technical concept of the present invention is:
[0019] On the positive electrode side, positive electrode material coating and other means are usually used to alleviate the interfacial side reactions between sulfide electrolyte and positive electrode materials under high voltage. In practical sulfide solid-state batteries, in order to match high-voltage application scenarios, the intermediate layer of the sulfide electrolyte membrane needs to be modified to improve the high-voltage resistance of the electrolyte membrane. The development of high-voltage resistant sulfide electrolyte membranes can support higher operating voltages. This helps to increase the energy density of the battery, allowing the battery to store more energy at the same volume or weight, thereby improving the performance and endurance of the battery. By designing an asymmetric double-layer electrolyte membrane, the sulfide electrolyte layer can be specially designed to be highly conductive by combining two different electrolyte materials, while the modified layer is mainly close to the positive electrode side to improve the high-voltage resistance of the electrolyte membrane, thereby improving the overall performance of the sulfide all-solid-state battery.
[0020] In the technical solution provided by the present invention, a binder-solvent system compatible with high-voltage resistant systems such as halide electrolytes / polymer electrolytes and sulfide electrolytes is selected, and a high-voltage resistant protective layer is prepared in situ on the surface of the sulfide electrolyte membrane layer by wet coating, electrostatic spraying, ultrasonic spraying and other methods, thereby reducing the introduction of additional steps in the original sulfide electrolyte membrane preparation process as much as possible; by introducing the high-voltage protective layer, the sulfide electrolyte membrane has the characteristics of high-voltage resistance, and the thickness of the high-voltage resistant electrolyte membrane increases within a controllable range; by regulating the modification method of the high-voltage protective layer, a uniform and dense high-voltage protective layer can be formed on the surface of the sulfide electrolyte membrane, which can achieve a better high-voltage resistance effect; finally, a double-layer electrolyte membrane modified with a high-voltage protective layer can be prepared, and an all-solid-state battery with high voltage and high energy density can be prepared by the electrolyte membrane. The invention has broad application prospects in the fields of solid-state lithium-ion battery preparation and the like. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of a high-voltage all-solid-state battery constructed with a double-layer electrolyte membrane prepared by the present invention;
[0022] Figure 2 This is a SEM image of the high-pressure resistant sulfide electrolyte membrane prepared in Example 1;
[0023] Figure 3 This is a test diagram of the first three charge and discharge cycle tests in Example 1. DETAILED DESCRIPTION
[0024] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention, rather than to limit the present invention.
[0025] Embodiment 1:
[0026] Li 3 InCl 6 The electrolyte and the PIB binder were mixed evenly in a mass ratio of 98:2 to obtain a mixture A. Xylene solvent was added to the mixture A and stirred evenly by a double planetary mixer. The slurry viscosity was controlled within the range of 1000-1500 mPa·s to obtain a modified layer slurry B. The slurry B was filtered and added to an ultrasonic spraying device. The slurry B was sprayed on the Li 6 PS 5 Cl sulfide electrolyte membrane surface, control the spraying time to 2 seconds, and obtain double-layer electrolyte membrane C. Transfer double-layer electrolyte membrane C to a vacuum oven, draw the vacuum degree to -0.085mbar, set the heating program, control the heating rate to 1℃ / min to 60℃ in the first stage, and keep the temperature constant for 60min; control the heating rate to 10℃ / min to 100℃ in the second stage, and keep the temperature constant for 4h to obtain a dried high-pressure sulfide electrolyte membrane. Cut the high-pressure electrolyte membrane into a size of 4.2×6.2cm, and place the Li-based 1.2 Ni 0.13 Co 0.13 Mn 0.54 O 2 The positive electrode sheet is cut into a size of 4.0×6.0cm, and the nano-silicon-based negative electrode sheet is cut into a size of 4.2×6.2cm. The three layers of electrode sheets are stacked in sequence and vacuum packaged in an aluminum-plastic film. The solid-state battery is densified under the conditions of an isostatic pressing temperature of 80°C, a pressure range of 500MPa, and a pressing time of 5min. After densification, the solid-state battery is subjected to battery testing. First, an electrochemical workstation is used to test the interface resistance of the solid-state battery with a test frequency range of 5MHz to 0.1Hz. The prepared battery is further charged and discharged at a current density of 0.1C and a test temperature of 25°C. The charge and discharge range is 2.0 to 4.7V (vs.Li + / Li).
[0027] Embodiment 2:
[0028] The difference from Example 1 is that the binder in mixture A is PMMA.
[0029] Embodiment 3:
[0030] The difference from Example 1 is that the binder in mixture A is SBR.
[0031] Embodiment 4:
[0032] Li 3 InCl 6The electrolyte and the PIB binder were mixed in a mass ratio of 98:2 to obtain a mixture A. Xylene solvent was added to the mixture A and stirred evenly by a double planetary mixer. The slurry viscosity was controlled within the range of 2000-3000 mPa·s to obtain a modified layer slurry B. The slurry B was sprayed on the Li 6 PS 5 Cl sulfide electrolyte membrane surface, control the scraper gap to 20 ~ 30μm, and obtain double-layer electrolyte membrane C. Transfer double-layer electrolyte membrane C to a vacuum oven, draw the vacuum degree to -0.085mbar, set the heating program, in the first stage, the heating rate is controlled to 1℃ / min to 60℃, and the temperature is kept constant for 60min; the second stage heating rate is controlled to 10℃ / min to 100℃, and the temperature is kept constant for 4h to obtain a dried high-pressure sulfide electrolyte membrane. Cut the high-pressure electrolyte membrane into a size of 4.2×6.2cm, and the Li-based 1.2 Ni 0.13 Co 0.13 Mn 0.54 O 2 The positive electrode sheet is cut into a size of 4.0×6.0cm, and the nano-silicon-based negative electrode sheet is cut into a size of 4.2×6.2cm. The three layers of electrode sheets are stacked in sequence and vacuum packaged in an aluminum-plastic film. The solid-state battery is densified under the conditions of an isostatic pressing temperature of 80°C, a pressure range of 500MPa, and a pressing time of 5min. After densification, the solid-state battery is subjected to battery testing. First, an electrochemical workstation is used to test the interface resistance of the solid-state battery with a test frequency range of 5MHz to 0.1Hz. The prepared battery is further charged and discharged at a current density of 0.1C and a test temperature of 25°C. The charge and discharge range is 2.0 to 4.7V (vs.Li + / Li).
[0033] Embodiment 5:
[0034] The difference from Example 1 is that the halide electrolyte used in mixture A is Li 3 ZrCl 6 .
[0035] Comparative Example 1:
[0036] The difference from Example 1 is that no additional modification layer slurry B is introduced, and the unmodified Li 6 PS 5 Cl sulfide electrolyte membrane was used for interfacial impedance testing and assembled all-solid-state battery testing.
[0037] Table 1 Performance parameter statistics of the embodiments and comparative examples
[0038]
[0039]
[0040] like Figure 2 As shown, it can be clearly seen in the SEM image that the prepared high-voltage resistant sulfide electrolyte membrane is composed of a double layer, and there is a 10μm thick high-voltage modification layer on the surface; as shown in Table 1, compared with Comparative Example 1, although the introduction of the high-voltage modification layer in Examples 1, 2 and 3 will cause the ionic conductivity of the sulfide electrolyte membrane to decrease, it plays an important role in the performance of the all-solid-state battery at high voltage. The modification layer can effectively inhibit the occurrence of side reactions at high voltage and inhibit the continuous increase of interface impedance. Compared with Example 4, Example 1 can achieve similar effects by introducing a high-voltage protective layer on the surface of the sulfide electrolyte membrane using different modification methods, but due to the differences in the modification methods, the thickness of the high-voltage modification layer is different, so the degree of influence on the ionic conductivity index of the high-voltage resistant electrolyte membrane is different. Compared with Example 5, the use of different types of halides in Example 1 has certain differences in the performance of high-voltage all-solid-state batteries, but the first cycle charge capacity exceeds 260mAh / g, showing high voltage stability.
[0041] The above description is only a preferred embodiment of the present invention and cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.
Claims
1. A method for preparing a high-conductivity, high-voltage resistant sulfide electrolyte membrane, characterized in that: The following steps are involved: (1) Prepare sulfide electrolyte membrane by wet slurry coating or dry electrode technology; (2) using a halide electrolyte or a polymer electrolyte as the raw material for the high voltage modification layer, and directly in-situ modifying the prepared modification layer slurry on the surface of the sulfide electrolyte membrane; (3) The modified electrolyte membrane is transferred to a dry atmosphere and baked to obtain an asymmetric high-pressure resistant sulfide electrolyte membrane.
2. The method according to claim 1, characterized in that In step (1), the sulfide electrolyte includes Li7P3S 11 ,β-Li3PS4,Li 10 GeP2S 12 , Li6PS5Cl, Li6PS5Br, Li7P2S8I, Li4PS4I, Li6PS5Cl x Br 1-x 、Li6PS5Cl y I 1-y 、Li6PS5Br z I 1-z One or more of , where x, y, z = 0 to 1.
3. The method according to claim 1, characterized in that In step (2), the halide electrolyte used is Li3MX6, wherein M includes one or more trivalent metals of indium, scandium, yttrium, titanium, and zirconium, and X includes one or more of Cl, Br, and I.
4. The method according to claim 1, characterized in that In step (2), during the preparation of the polymer electrolyte modification layer, the selected polymer electrolyte system includes one or more of polyvinyl fluoride, polyacrylonitrile, polyether electrolyte, and cross-linked polyurethane.
5. The method according to claim 1, characterized in that In step (2), in the process of preparing the modifying layer slurry, a binder-solvent solution needs to be added, wherein the solvent includes one or more of isopentane, n-pentane, cyclohexane, isooctane, cyclopentane, n-hexane, n-heptane, tetrahydrofuran, toluene, xylene, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dichloromethane, chloroform, n-butyl ether, and anisole, and the binder includes one or more of polyisobutylene, butadiene rubber, nitrile rubber, thermoplastic elastomer, styrene-butadiene rubber, polyvinylidene fluoride, polyisobutylene, thermoplastic styrene-butadiene rubber, synthetic rubber, hydrogenated nitrile rubber, polyethylene-vinyl acetate, polymethyl methacrylate, and polyacrylic acid.
6. The method according to claim 1, characterized in that In step (2), the selected modification method includes one or more of wet coating, electrostatic spraying, and ultrasonic spraying.
7. The method according to claim 1, characterized in that In step (3), a gradient temperature rise program is set during baking. In the first stage, the temperature is raised to 60-80°C at a heating rate of 0.1-20°C / min and the temperature is kept constant for 20-120 minutes; in the second stage, the temperature is raised to 90-130°C at a heating rate of 0.1-20°C / min and the temperature is kept constant for 2-6 hours.
8. The method according to claim 1, characterized in that The thickness of the high-pressure sulfide electrolyte membrane is 20 to 200 μm, and the room temperature conductivity is 10 -6 ~10 -1 S / cm.
9. A high voltage all-solid-state battery, characterized in that: It comprises a high-voltage sulfide electrolyte membrane, a high-voltage positive electrode and a negative electrode prepared by the method according to any one of claims 1 to 8, wherein the high-voltage positive electrode layer, the high-voltage sulfide electrolyte membrane and the negative electrode layer are stacked in sequence, and densified by isostatic pressing technology to obtain an all-solid-state battery capable of operating at high voltage, wherein the modified layer in the high-voltage sulfide electrolyte membrane is close to the positive electrode side.
10. The high voltage all-solid-state battery according to claim 9, characterized in that: The high-voltage positive electrode selects one or more of LiCoO2, LiNi a Co b M 1-a-b O2, and Li 1+n (Mn X Ni Y Co Z ) 1-n O2, where M is one or more of Mn, Al, Mg, Sn, Y, or Cr, 0 ≤ a < 1, 0 < b ≤ 1, and a + b ≤ 1; 0 < n < 1, 0 < X < 1, X + Y + Z = 1, 0 < Y < X, 0 < Z < X; the negative electrode selects one or more of lithium metal alloy, lithium metal, graphite, silicon-carbon composite negative electrode, and silicon; during the densification process of the high-voltage all-solid-state battery during the isostatic pressing process, the isostatic pressing temperature is 0 to 100 °C, the pressure range is 300 to 800 MPa, and the pressing time is 1 to 30 min.
Citation Information
Patent Citations
All-solid-state lithium battery and preparation method thereof
CN115207456A
Composite solid electrolyte film and preparation method and application thereof
CN115458801A
Composite electrode, preparation method thereof and all-solid-state battery
CN116314589A
Preparation method of sandwich type composite solid electrolyte membrane
CN118572174A
Cited By
Sulfide electrolyte membrane with high compaction density at room temperature, preparation method of sulfide electrolyte membrane and solid-state battery
CN121035334A